2020
DOI: 10.3390/nano10122387
|View full text |Cite
|
Sign up to set email alerts
|

Silicon-Carbide (SiC) Nanocrystal Technology and Characterization and Its Applications in Memory Structures

Abstract: Colloidal cubic silicon-carbide nanocrystals have been fabricated, characterized, and introduced into metal–insulator–semiconductor and metal–insulator–metal structures based on hafnium oxide layers. The fabricated structures were characterized through the stress-and-sense measurements in terms of device capacitance, flat-band voltage shift, switching characteristics, and retention time. The examined electrical performance of the sample structures has demonstrated the feasibility of the application of both typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In addition, the ultra-thin tunnel oxide layer in the nanocrystal floating-gate memory has the advantages of low power consumption and high erasing/programming speed [ 9 , 10 , 11 ]. The research on nanocrystal floating-gate memory is extensive, from traditional silicon germanium materials to third-generation semiconductor materials of SiC [ 15 , 16 , 17 ]. As reported by Jin et al [ 15 ], floating-gate memory based on antimony-doped tin oxide nanoparticles has a maximum memory window of 85 V. However, there are 40 program/erase cycles, which has not been tried in 3D NAND devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the ultra-thin tunnel oxide layer in the nanocrystal floating-gate memory has the advantages of low power consumption and high erasing/programming speed [ 9 , 10 , 11 ]. The research on nanocrystal floating-gate memory is extensive, from traditional silicon germanium materials to third-generation semiconductor materials of SiC [ 15 , 16 , 17 ]. As reported by Jin et al [ 15 ], floating-gate memory based on antimony-doped tin oxide nanoparticles has a maximum memory window of 85 V. However, there are 40 program/erase cycles, which has not been tried in 3D NAND devices.…”
Section: Introductionmentioning
confidence: 99%
“…The memory window of 3.8 V shows a very slow capacitance decease, which is not adopted in 3D NAND devices. According to the research of Andrzej et al [ 17 ], a nanocrystalline SiC floating-gate memory exhibits better charge retention characteristics than the conventional floating-gate memory. However, the program/erase speed is in the scale of S, which is not applied in 3D NAND memory.…”
Section: Introductionmentioning
confidence: 99%
“…By simply scanning a pristine polymer, composite structures composed of carbon-based NCs can be directly patterned, allowing for the rapid fabrication of flexible devices. Previously, it has been indicated that if the irradiated polymer is a silicone polymer, namely, polydimethylsiloxane (PDMS), the resulting composite structure can also contain silicon carbide NCs (SiC-NCs). Bulk SiC is a well-known semiconductor already implemented in a variety of commercially available electronic and photonic devices. In recent years, SiC-NCs have slowly been gaining attention as an up-and-coming material with the potential to outperform previously existing NCs. , Although the number of studies regarding SiC-NCs is still relatively less compared to that of other NCs, the presently reported results are highly promising and indicate the advantages of using SiC-NCs for semiconducting electronic units, solar cells, and fluorescence-based sensors . However, for the structures patterned by the laser-induced modification of silicone polymers, material properties distinctive of SiC-NCs have not been reported, possibly due to the low SiC-NC content.…”
Section: Introductionmentioning
confidence: 99%
“…Materials as well as innovative applications combining different areas of nanotechnology are invited. Scientists as well as engineers are brought together from different disciplines such as materials science, forensic engineering, biomedical engineering, chemical engineering, electrical engineering, physics, microtechnology, nanorobots and nanosensors [ 1 , 2 , 3 ]. Different researchers have developed different types of nanoparticles, namely Nanoparticles are categorized into various categories depending on their size, morphology, physical, and chemical properties.…”
Section: Introductionmentioning
confidence: 99%